“If It Happens Again I’m Leaving”: Suggestions for Risk Communication from a Field Study of Communities in Basilicata, Italy - Scolozzi, Rocco (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
Risk communication plays a crucial role in preparing for and managing disaster events as well as in building trust between citizens and institutions. Natural disasters can trigger processes of land abandonment or further weaken already fragile communities. The preparedness and resilience and adaptability of communities in the face of events such as landslides, floods, or earthquakes depend on a number of variables, such as: widespread perception of risks, reciprocity and trust between citizens and between citizens and institutions, available resources (human and material), and collective preparedness and application of functional behaviors. The objective of the research presented here, part of the MITIGO project, was to gather elements useful in defining communication and self-protection models that can increase community resilience. To gather elements regarding these processes, a questionnaire was defined and administered in four small municipalities in Basilicata. The questionnaire made it possible not only to find some answers to the research questions but also to ask new ones; for example, it made it possible to identify some crucial aspects, such as: the variability in the number of inhabitants actually in their municipality between holidays and working days and between different time slots, the different level of trust in the municipal administration and in institutions in general, and the different degree of knowledge of risks and behaviors to be implemented in case of emergency. Reciprocity among inhabitants also differed. Communities in fragile territories have recurring differences; these differences if recognized can guide more effective risk communication and community resilience support programs. After an overview of risk communication theories and models, some useful suggestions are presented for setting up risk communication projects specific to the explored communities and similar inland areas of Basilicata or mountain areas in general.